2003
DOI: 10.1093/sleep/26.8.986
|View full text |Cite
|
Sign up to set email alerts
|

Total Sleep Deprivation Elevates Blood Pressure Through Arterial Baroreflex Resetting: a Study with Microneurographic Technique

Abstract: The diastolic blood pressure increased and both burst rate and burst incidence of MSNA decreased after total sleep deprivation. The results show that resetting of the ABR toward a higher blood pressure level occurred after total sleep deprivation. This ABR resetting probably brings about an increase in arterial blood pressure after total sleep deprivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
133
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(151 citation statements)
references
References 15 publications
11
133
0
7
Order By: Relevance
“…These effects, however, were restricted to the first half of total sleep time, and it is unlikely that this small effect sustained throughout the second half of the night. Previous studies consistently demonstrated that total 17,26 or partial 6,27 sleep deprivation resulted in increased blood pressure the next day, whereas the subjects in our study with less SWS had lower blood pressure levels.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…These effects, however, were restricted to the first half of total sleep time, and it is unlikely that this small effect sustained throughout the second half of the night. Previous studies consistently demonstrated that total 17,26 or partial 6,27 sleep deprivation resulted in increased blood pressure the next day, whereas the subjects in our study with less SWS had lower blood pressure levels.…”
Section: Discussionsupporting
confidence: 58%
“…2,9,15 Several studies suggested that nocturnal blood pressure dipping is caused by a shift of the baroreflex set point toward lower blood pressure levels. 9,14,17 However, the question remains unresolved regarding whether this is an active process or the mere consequence of physical inactivity and sleep-related deprivation from external stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of SWS could attenuate dipping, and therefore inhibit mechanisms of baroreflex-mediated blood pressure resetting. Both fragmentation of sleep due to repetitive arousals as well as sleep deprivation result in nocturnal sympathoexcitation leading to a nondipping profile and increased blood pressure even during daytime (12,16,36). The latter has repeatedly been shown for conditions of sleep-disordered breathing and was hypothesized to reflect a pathophysiologic adaptation to the increased nocturnal sympathetic activity (2,19).…”
mentioning
confidence: 97%
“…Baroreflex mechanisms are increasingly recognized to be involved in the medium-term regulation of blood pressure in addition to their role in buffering acute blood pressure changes (17,24). The proper resetting of the baroreflex threshold during NREM sleep is probably one key factor for the beneficial effects of sleep-related blood pressure dipping on cardiovascular health (15,16) and was found to exert stabilizing effects for blood pressure regulation during the daytime period (22). Sleep disturbances, in contrast, are linked to deficits in blood pressure regulation.…”
mentioning
confidence: 99%
“…Experimentelle Daten zeigen zudem, dass Schlafentzug und eine reduzierte nächtliche Schlafzeit mit Anstiegen des Blutdrucks [22] und der C-reaktiven Proteinkonzentrationen [23] …”
Section: Folgen Des Gestörten Schlafsunclassified